The grounds of classification of interbranch principles of the right (Journal of actual problems of jurisprudence, 2018)
The article discusses the Foundation of the classification of interbranch principles of the right: namely, the interdisciplinary principles in the economic, social, cultural, political spheres. The author considers different points of view of scientists-lawyers on this issue. At the present time is particularly acute issue of rights according to the objective laws of economic development. The necessary condition for the effectiveness of law – the strict observance of the right laws. Interbranch principles of law, have a decisive impact on the cultural sphere are as follows: ensuring the freedom of literary, artistic, scientific, technical creativity and teaching; providing free access to education and cultural values. These principles are interdisciplinary in nature, as are manifested in the civil law (for example, they need to be taken into account at the conclusion of civil contracts for training in higher educational institutions, etc.), administrative (with the legal regulation of the education system, creating university, museum complexes, etc.), labor (principles appear at the conclusion of employment contracts, tax law (principles should be taken into account, such as the provision of tax benefits), as a whole, where it is related to education and culture.Key words: the principle rights, the rule of law, branch of law, system of law.